PENGARUH EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav.) TERHADAP GLUKOSA DARAH MENCIT (Mus musculus L.) JANTAN YANG DIINDUKSI SUKROSA - Muhammad Rizki Saputra; Ramadhan Sumarmin (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
Patients withdiabetes mellitus(DM) continues to grow becauseprosperityandpeople's lifestyles.Treatment of diabetesoften useinjectionsof insulinandoralantidiabeticdrugs. Thetreatmenthas no side effects. Therefore, it isnecessary to findeffective drugsusing plantsthatred betelleaf(Piper crocatumRuiz&Pav.). Red betel leafcontains flavonoidswhichare antioxidants. This study aimsto determine the effectand dose ofextractof redbetel leaf(Piper crocatumRuiz&Pav.) The mosteffectiveagainstbloodglucosein mice(Mus musculusL.) maleinducedsucrose.This study was an experimental study. The research was conducted in October 2015 in the Division of Laboratory Animal and Zoology Department of Biology, State University of Padang. The subject of research in the form of mice (Mus musculus L.) males totaled 24 tails. The design used was completely randomized design (CRD) with 6 treatments and 4 repetitions. The treatment is given as follows: treatment I: the diabetes control without any treatment given, treatment II: as a negative control (sucrose 3 g/kg bw), treatment III: sucrose+suspension of red betel leaf extract (dosage 0,7 g/kg bw), treatment IV: sucrose+suspension of red betel leaf extract (dosage 1,4 g/kg bw), treatment V: sucrose+suspension of red betel leaf extract (dosage of 2,1 g/kg bw) and treatment VI: sucrose+suspension extracts red betel leaf (dosage 2,8 g/kg bw).The results showed that the extract of red betel leaf (Piper crocatum Ruiz & Pav.) at a dose of 0,8 g/kg bw 1,4 g/kg bw 2,1 g/kg bw and 2,8 g/kg bw can lowers blood glucose in mice. However, the most appropriate dose in lowering blood glucose in mice (Mus musculus L.) at 2,8 g/kg bw in mice.